Presentation of the new ICARUS member - Faculty of Humanities and Social Sciences, University of Zagreb - Department of Information and Communication Sciences - Stančić, Hrvoje (2012)
New ICARUS member - Faculty of Humanities and Social Sciences, University of Zagreb - Department of Information and Communication Sciences was presented at the ICARUS meeting.